CHARACTERISATION USING LEITMOTIFS IN FINAL FANTASY IX - Niemenrinne, Pinja (My University, 2021)
The purpose of this study is to investigate how characterisation is done using leitmotifs in the Japanese role-playing game, Final Fantasy IX (2000). The term role playing game is used to refer to console role-playing games in this study. The subject is approached by analytical play and audiovisual analysis. In Final Fantasy IX, characterisation using musical character themes, or leitmotifs plays a fairly important role. Each one of the eight playable characters has their own designated character theme, which builds the basis for each character’s persona. The leitmotifs are then located from other pieces of music and using these leitmotifs, the characters are then tied to certain events, places, or other characters during the game. These events, places, or character relations then reveal how the eight playable characters develop through the game, and how the story is told using music. What was discovered, was how important leitmotifs are, not only in characterisation, but also in character development, and storytelling. It is important to highlight the role and importance of music, not only as a passive element playing in the background but as an active element, telling a story and describing characters and their connections and relationships.

Tutkielman tarkoitus on selvittää, miten hahmojen kuvausta tehdään johtoaiheiden avulla japanilaisessa roolipelissä, Final Fantasy IX:ssä (2000). Roolipeli-termillä viitataan tässä tutkielmassa ensisijaisesti konsoliroolipeleihin. Aihetta lähestytään analyyttisellä pelaamisella ja audiovisuaalisella analyysillä. Final Fantasy IX:ssä hahmojen kuvaamisella musiikillisten teemojen, tai johtoaiheiden avulla on tärkeä merkitys. Jokaisella kahdeksasta pelattavasta hahmosta on oma hahmoteemansa, jonka pohjalle rakentuu jokaisen hahmon persoona. Nämä johtoaiheet sitten etsitään muista kappaleista ja niitä avuksi käyttäen hahmot yhdistetään tiettyihin tapahtumiin, paikkoihin ja jopa toisiin hahmoihin pelin aikana. Nämä tapahtumat, paikat, tai hahmojen väliset suhteet sitten osoittavat miten, kahdeksan pelattavaa hahmoa kehittyvät pelin aikana ja kuinka tarinaa kerrotaan musiikin avulla. Tutkimuksessa selvisi, kuinka tärkeä osa peliä johtoaiheet ovat, eivät pelkästään hahmojen kuvauksessa, mutta myös hahmojen kehityksen kuvaamisessa ja tarinankerronnassa. On tärkeää korostaa musiikin roolia ja merkitystä, ei vain passiivisena elementtinä taustalla, mutta aktiivisena elementtinä, joka kertoo tarinaa ja kuvailee hahmoja, kyseisten hahmojen liitoksia ja suhteita.
Keywords: video game music, leitmotif, audiovisual analysis, final fantasy, role-playing game